Validation of a Traditional Medicine, Achyrocline satureioides Infusion, for the Improvement of Mild Respiratory Infection Symptoms: A Randomized, Placebo-Controlled and Open-Label Clinical Trial - Catherina Isdra Moszkowicz Bastos; Caroline Dani; Laura Reck Cechinel; Arthur Hipolito da Silva Neves; Fabiana Briato Rasia; Marcelo Lazzaron Lamers; Sara Elis Bianchi; Gabriela Meirelles; Paulo Valdeci Worm; Valquiria Linck Bassani; Ionara Rodrigues Siqueira (Pharmaceuticals, 2025)
Background/Objectives: The need for the scientific validation of traditional and folk medicine knowledge has emerged lately. Achyrocline satureioides inflorescences have been widely used for the management of mild viral respiratory infection symptoms in South Brazil, Uruguay and Argentina. We intended to assess the therapeutic efficacy of a 14-day course with A. satureioides for mild viral respiratory infection symptoms. Methods: We conducted a randomized, open-label, placebo-controlled trial. Before COVID-19 (SARS-CoV-2) diagnostic tests, participants were randomly assigned to one of two experimental groups: A. satureioides or Malus domestica infusions, with instructions to use the infusions twice a day for 14 days. Our primary endpoint was the recovery time for respiratory symptoms in the overall analysis; the secondary outcomes were the recovery time for non-respiratory symptoms and for stratified analysis, taking into account the vaccination status against SARS-CoV-2 and COVID-19 infection; and the rate of symptom recovery was also evaluated. Results: The A. satureioides infusion significantly accelerated the resolution of sore throat and sneezing compared with the control group. The participants with COVID-19 who had not been vaccinated and received A. satureioides infusion recovered faster from sore throat, body ache, fever and cough, and showed a shorter median survival time for symptom resolution. The SARS-CoV-2-negative group that received A. satureioides had a faster improvement in the survival analysis of sore throat, earache and loss of appetite. Conclusions: Our findings support the hypothesis that Achyrocline satureioides inflorescence infusions may offer therapeutic benefits in the management of mild viral respiratory infections, as its administration was associated with a significantly accelerated resolution of clinical symptoms. This study was registered in the Brazilian Registry of Clinical Trials (ReBEC; registration number RBR-8g6f2rv) on 27 January 2022.